Electrostatic Self-assembly of 0D–2D SnO2 Quantum Dots/Ti3C2Tx MXene Hybrids as Anode for Lithium-Ion Batteries - Liu, Huan; Zhang, Xin; Zhu, Yifan; Cao, Bin; Zhu, Qizhen; Zhang, Peng; Xu, Bin; Wu, Feng; Chen, Renjie (Nano-Micro Letters, 2019)
MXenes, a new family of two-dimensional (2D) materials with excellent electronic conductivity and hydrophilicity, have shown distinctive advantages as a highly conductive matrix material for lithium-ion battery anodes. Herein, a facile electrostatic self-assembly of SnO2 quantum dots (QDs) on Ti3C2Tx MXene sheets is proposed. The as-prepared SnO2/MXene hybrids have a unique 0D–2D structure, in which the 0D SnO2 QDs (~ 4.7 nm) are uniformly distributed over 2D Ti3C2Tx MXene sheets with controllable loading amount. The SnO2 QDs serve as a high capacity provider and the “spacer” to prevent the MXene sheets from restacking; the highly conductive Ti3C2Tx MXene can not only provide efficient pathways for fast transport of electrons and Li ions, but also buffer the volume change of SnO2 during lithiation/delithiation by confining SnO2 QDs between the MXene nanosheets. Therefore, the 0D–2D SnO2 QDs/MXene hybrids deliver superior lithium storage properties with high capacity (887.4 mAh g−1 at 50 mA g−1), stable cycle performance (659.8 mAh g−1 at 100 mA g−1 after 100 cycles with a capacity retention of 91%) and excellent rate performance (364 mAh g−1 at 3 A g−1), making it a promising anode material for lithium-ion batteries. Highlights: 1 0D–2D SnO2 quantum dots/MXene (SnO2 QDs/MXene) hybrids were synthesized by electrostatic self-assembly. 2 MXene not only provides efficient pathways for fast transport of electrons and Li ions, but also buffers the volume change of SnO2 during charge/discharge process. 3 The 0D–2D SnO2 QDs/MXene hybrids deliver high capacity, excellent cycle and rate performances as anode of lithium-ion batteries.